(untitled) (Research, Society and Development, 2021)
Photoanthropometry quantify the facial proportions of an individual facilitating the comparison of facial patterns for human identification. The coordinates and vertical distances in pixels of the photoanthropometric landmarks on images of the same individual in frontal and profile views were analyzed and compared. A total of 116 pairs of photographs of Brazilian individuals were evaluated. The photographs were adjusted in size and rotation, and marked in the software Two-dimensional Forensic Facial Analysis System. For each face, 16 landmarks were considered: glabella (g), nasion (n), ectocanthion (ec), pronasale (prn), subnasale (sn), alare (al), cheilion (ch), upper lip (ls), lower lip (li), stomion (sto), labiomental (lm), gnathion (gn), superaurale (sa), subaurale (sba), postaurale (pa) and upper ear lobe (slb); the x- and y-coordinates of each landmark were obtained. Twenty-seven vertical distances between the points were proposed, which were measured by subtracting the values of the y-coordinate. The data were analyzed descriptively and inferentially using the Kolmogorov-Smirnov test, intraclass correlation coefficient (ICC) and Mann-Whitney test (α=5%). The mean age of the sample was 25.9 years (± 4.7), and 50.9% (n=59) were males. When the coordinates were evaluated, a low correlation was obtained between the images (ICC<0.4). Of the 27 proposed measures, 77.7% (n=21) indicated agreement between the images in the two views (p>0.05). A comparison of ls-g, sa-ec, pa-ec, slb-ec, sba-sa and slb-sa showed disagreement between the images. Therefore, there is agreement between the facial measures in the frontal and lateral images, except for ls-g and for the distances between the ear landmarks.